Diaporthe atlantica improves tomato resistance against the vascular pathogen Fusarium oxysporum f. sp. lycopersici - Eric C. Pereira; Beatriz R. Vázquez de Aldana; Juan B. Arellano; Ivan Fernandez; Iñigo Zabalgogeazcoa (Biological Control)
Fungal pathogen attacks are a major threat to crop growth and productivity, with Fusarium oxysporum f. sp. lycopersici being particularly menacing to tomato plants by causing vascular wilt disease. Diaporthe atlantica is a main component of the root microbiome of Festuca rubra subsp. pruinosa, a grass which inhabits sea cliffs. This fungus can confer drought and salinity tolerance to some agricultural plant species. This study evaluated the efficacy of Diaporthe atlantica in conferring resistance against Fusarium in tomato plants in a greenhouse experiment. A significant reduction of Fusarium wilt symptoms was observed in plants inoculated with Diaporthe. Furthermore, Diaporthe suppressed Fusarium colonisation, mitigating vascular browning and improving plant growth, chlorophyll content and nutrient acquisition. In addition, the effect of Diaporthe atlantica on plant defence against Fusarium does not directly involve classical induced systemic resistance (ISR) or systemic acquired resistance (SAR) mechanisms. These findings underscore the potential of Diaporthe as a biocontrol agent against Fusarium wilt.